Knowledge and attitude of senior dental students towards HIV/AIDS - Jafari A; Khami MR; Yazdani R; Mohammadi M (Tehran University of Medical Sciences, 2010)
Background and Aims: The objective of the present study was to investigate knowledge and attitude of senior dental students towards HIV/AIDS. Its result could help in promotion of education. Materials and Methods: This educational research was carried out in two state dental schools in Tehran. The senior dental students in Tehran and Shaheed Beheshti dental schools were asked to fill in a self-administered questionnaire regarding their age, gender, parents' job, knowledge and attitudes towards treatment of patients with HIV/AIDS in Autumn semester 2007. Fifty five dental students (83%) including 27% male and 73% female in Shaheed Beheshti and fifty five dental students (85%) including 34% male and 66% female in Tehran dental schools were participated. The score for knowledge and attitude of the students were calculated separately. The data were analyzed using Independent sample t-test. Results: The mean percentage of knowledge and attitude scores were 76.5% (at rang 1-3) and 50% (at range 1-5), respectively. Nearly all of the students believed that all patients should be considered as HIV positive in dental practice, while 49% preferred to refer HIV positive patients. Knowledge and attitude of students were not significantly associated with the gender and knowing HIV positive person (P>0.05). Conclusion: There is a need to improve knowledge and attitudes of dental students towards HIV/AIDS. It is suggested to emphasize on this subject in dental schools curriculum in Iran.